2010
DOI: 10.1007/s00011-010-0255-8
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous procalcitonin evokes a pro-inflammatory cytokine response

Abstract: Clinically relevant levels of ProCT influence immunologic responses that may contribute to systemic inflammatory response and septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…Pincíková et al [68] showed that PCT dose dependently decreased both phagocytic and candidacidal activity of neutrophils and supported the E. coli colony count increase during the incubation in the presence of both serum and blood. After exposure to PCT levels, consistent with septic shock (1,000 pM), directed migration of human neutrophils was decreased [64], and deactivation of chemotaxis of monocytes by pretreatment with PCT was also reported [66]. However, the PCT inflammatory concept is not yet unanimously accepted and may be much more complex.…”
Section: Biological Effects (Functions/properties) Of Pctmentioning
confidence: 90%
See 1 more Smart Citation
“…Pincíková et al [68] showed that PCT dose dependently decreased both phagocytic and candidacidal activity of neutrophils and supported the E. coli colony count increase during the incubation in the presence of both serum and blood. After exposure to PCT levels, consistent with septic shock (1,000 pM), directed migration of human neutrophils was decreased [64], and deactivation of chemotaxis of monocytes by pretreatment with PCT was also reported [66]. However, the PCT inflammatory concept is not yet unanimously accepted and may be much more complex.…”
Section: Biological Effects (Functions/properties) Of Pctmentioning
confidence: 90%
“…Again, few reports are available regarding the specific action of PCT, but hematopoietic cells have been postulated as one of the key cellular targets of PCT. Liappis et al [64] reported that treatment of human whole blood cells led to a significant release of proinflammatory cytokines, including TNFa, IL-1b, IL-6, and IL-8. This may explain the massive increase in levels of PCT following infection where bacteria induces proinflammatory cytokines that stimulate PCT release, which, in turn, trigger production of PCT itself, causing a positive loop of PCT secretion.…”
Section: Biological Effects (Functions/properties) Of Pctmentioning
confidence: 99%
“…Data from Sexton et al have provided a potential molecular mechanism for the observation that PCT appears to be toxic while CGRP treatment appears to be beneficial in animal models of sepsis [69]. Clinically relevant levels of PCT influence immunologic responses that may contribute to systemic inflammatory response and septic shock [72]. Of importance, immunologic blockade of CT precursors may offer a novel therapeutic approach to human sepsis [73].…”
Section: Biologic Role Of Procalcitoninmentioning
confidence: 99%
“…However, in response to bacterial and/or severe systemic inflammatory exposure, cells throughout the body secrete ProCT and its associated peptides (Table 1) [1]. In addition to this biomarker role in septic-like conditions, ProCT also appears to act as a biomediator, whereby it has direct and independent toxic effects on cells [2,3]. Although there has been ample documentation that serum ProCT increases multifold in various septic-like conditions, where it correlates with severity and mortality [1,4,5], there has been little attention drawn to the possible influence of baseline ProCT and its associated peptides that circulate at low concentrations in healthy individuals [6].…”
Section: Procalcitoninmentioning
confidence: 99%